The change of values in the west and the task of community personalism - Díaz Hernández, Carlos (2014)
The author analyzes the stages of the crisis of values considering four phases: the theocentric, characterized by blind faith, having as prototype to Abraham; the theo-anthropocentric, typical of the renaissance, the reformation and the enlightenment; the Promethean anthropocentrism; and the post- anthropocentric and post-theocentric of Narcissus, in which there is only the “I”, without God at the sight and whose features are: goodbye to the worldviews, relativism, individualism and the end of history. As a way out of this crisis, the vision of community personalism by E. Mounier is proposed, that conceives the person as a spiritual being, as absolute subject of values, being a valuein itself, divided into three axes: the value, the duty and the virtue. The community personalism is the counterpart of oppressive capitalism and abstract individualism.